2010
DOI: 10.1097/hnp.0b013e3181c8e491
|View full text |Cite
|
Sign up to set email alerts
|

When Do Nurses Refer Patients to Professional Chaplains?

Abstract: Nursing has historically realized the importance of spirituality in patient care, and more than other healthcare staff, they also have recognized the integral role of chaplains in meeting the spiritual needs of patients. The present study examines specific patient and family issues for which nurses make referrals to chaplains. A previously piloted questionnaire asking how often nurses and allied staff refer patients to chaplains was distributed to 133 staff members at a New York area hospital, the majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Therefore, the present results are more consistent with the findings of Galek et al, 17 in which hospital directors placed the great importance on making referrals to chaplains for situations involving loss, grief, and death. These present results are also consistent with the findings of Weinberger-Litman et al 14 In that study, nursing staff were most likely to make referrals to chaplains "for those kinds of issues that have long been regarded as the traditional role of chaplain-to care for patients who are dying" 14(p47) and for their families, and, similar to the present study, chaplain were referred least likely for treatment-related issues. 14 Head nurses refer in the present study to a chaplain when the medical treatment reaches its limits.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Therefore, the present results are more consistent with the findings of Galek et al, 17 in which hospital directors placed the great importance on making referrals to chaplains for situations involving loss, grief, and death. These present results are also consistent with the findings of Weinberger-Litman et al 14 In that study, nursing staff were most likely to make referrals to chaplains "for those kinds of issues that have long been regarded as the traditional role of chaplain-to care for patients who are dying" 14(p47) and for their families, and, similar to the present study, chaplain were referred least likely for treatment-related issues. 14 Head nurses refer in the present study to a chaplain when the medical treatment reaches its limits.…”
Section: Discussionsupporting
confidence: 95%
“…These present results are also consistent with the findings of Weinberger-Litman et al 14 In that study, nursing staff were most likely to make referrals to chaplains "for those kinds of issues that have long been regarded as the traditional role of chaplain-to care for patients who are dying" 14(p47) and for their families, and, similar to the present study, chaplain were referred least likely for treatment-related issues. 14 Head nurses refer in the present study to a chaplain when the medical treatment reaches its limits. This is especially obvious in life-threatening situations, when a patient is about to die.…”
Section: Discussionsupporting
confidence: 95%
“…A number of studies have examined the assessment of other professionals — physicians, nurses, social workers, and mental health professionals — regarding the contribution of spiritual care (Fitchett et al, 2011; Taylor et al, 2015; Fitchett, 2017; Willemse et al, 2018) and regarding when a referral should be made for spiritual care (Fogg et al, 2004; Flannelly et al, 2006; Galek et al, 2007, 2009; Vanderwerker et al, 2008; Weinberger-Litman et al, 2010; Fitchett et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…5,[10][11] Such assistance must be provided regardless of religious preference, situational circumstances, sex, ethnicity, socioeconomic conditions or any other personal characteristics, thus re-establishing the interaction between spirituality and health and promoting the rapid recuperation of the patients receiving inpatient treatment, which also improves the quality of life of those in a terminal phase, who tend to mobilize and express their spirituality in a more intense form, in situations of emotional and existential crisis. 4,12 It is necessary to emphasize that, in the United States and the United Kingdom, the chaplain is part of the interdisciplinary team for care to the patient, also having access to their medical records, in which they record their visits, assessments, interventions and other activities of spiritual assistance, this being a routine action within the hospitals. This fact does not yet occur in Brazil, where it may be verified that the chaplains seek the appropriate recognition of their profession and meet difficulties in accessing training courses and processes in the area.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is observed that spirituality is coupled with terminality, being an instrument of considerable relevance, given that it assists in the process of coping, of being at peace, and of having hope in the light of the occurrences. 5,12,[15][16] Thus, considering that the hospital chaplaincy is becoming an emerging service in Brazilian health institutions, which needs the implantation of a formal organization or institution, as it is already in place in other countries, and in the light of the scale of the chaplaincy, linked to the aspect of spirituality in the care process for the terminal patient, this study has the aim of contributing to the discussion of this issue in the health field. In the light of the above, the study had as its objectives: to identify the chaplains' understanding in relation to spirituality; and to analyze the contribution of the chaplaincy to the care of terminal patients.…”
Section: Introductionmentioning
confidence: 99%